Implementasi Teknologi Kontainer Docker pada Server RADIUS untuk Manajemen Autentikasi Terpusat pada Jaringan MikroTik - Andreas Damar Saputra; Febrian Wahyu Christanto (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
The management of network infrastructure in the Semarang City Government includes 468 router sites that are managed collectively by only 7 technical personnel. The main challenge arises in meeting the Service Level Agreement (SLA) target of 99.5%, where 30 sites experienced downtime exceeding the tolerance limit of 3.72 hours due to the difficulty of local authentication coordination. This study implements a modified Network Development Life Cycle (NDLC) method, including analysis, design, laboratory simulation, and functional testing phases. As a validation phase, the system was tested in a laboratory environment integrated with 3 router sites. The test results show that the system successfully integrates FreeRADIUS, MariaDB, and daloRADIUS within a single management gateway. Based on the efficiency analysis, the RADIUS response time test yielded an average of 1142.83 ms with a difference of 211.95 ms from local authentication, thus remaining within a safe range for network operations. In addition, a satisfaction survey of technical personnel showed positive results with 75% expressing satisfaction and 25% quite satisfied. In conclusion, this Dockerized RADIUS model is worthy of recommendation as a standardization solution to accelerate troubleshooting and maintain public service availability.